Does Stability Matter More Than Spending? Public Investment Volatility, State Capacity, and Structural Transformation in Africa - Xianming Pan; Victor Oluwatayo Babalola; Kazeem Bello Ajide (African Development Review, 2026)
ABSTRACT While public investment is widely regarded as a catalyst for structural transformation, far less attention has been devoted to whether the stability of such investment matters as much as its magnitude. This study examines the relationship between public investment volatility, state capacity and structural transformation in Africa using an unbalanced panel of 46 countries covering 2000–2023. Employing Fixed Effects, Driscoll–Kraay, Correlated Random Effects, System‐GMM and panel threshold estimators, the analysis distinguishes between the effects of public investment levels and fluctuations in investment expenditure. The results indicate that public investment volatility is negatively associated with structural transformation, whereas public investment levels exhibit a positive association. State capacity emerges as an important conditioning factor, with the adverse association between investment volatility and structural transformation becoming significantly weaker in countries characterised by stronger institutional capacity. Threshold estimates further reveal that the relationship varies across institutional regimes, while regional analyses indicate stronger associations in Central, West and East Africa. The findings underscore the importance of investment stability alongside investment scale and suggest that capable state institutions play a critical role in supporting Africa's structural transformation process.